TRANSFORMASI DAN PROSES PEWARISAN PERTUNJUKAN TEATER TRADISIONAL LONGSER - D. Nurfajrin Ningsih; Arif Firmansyah (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the changes in Longsér based on its development, and how the process of inheriting Longsér is carried out by the Sunda Kiwari Theater. In the show, Longser is delivered in the local language, namely Sundanese which tells about everyday life. The Longsér group that has been known is the Panca Warna group. This study uses a qualitative approach with analytical descriptive method. The data collection technique is based on the results of observations and interviews with the Sunda Kiwari theater. The traditional Longsér theater performance by Teater Sunda Kiwari has been transformed into a more modern form according to the demands of the market and the wishes of the people. Based on the six aspects studied, almost all aspects of the structure underwent a transformation, such as changes using text/scripts, director intervention, and a more modern stage setting.